(untitled) (Editora Impacto Científico, 2025)
This study aimed to analyze the temporal dynamics and volatility of arabica coffee prices in Brazil between 2015 and 2024, based on monthly data from CEPEA/ESALQ-USP. Through descriptive and graphical analyses, two distinct periods were identified: from 2015 to 2020, prices showed relative stability, with low variability and averages between 106 and 146 USD/sack; from 2021 onwards, a transition to a regime of sharp appreciation and greater volatility was observed, with average prices reaching 260 USD/sack in 2024 and high coefficients of variation. Monthly analysis revealed seasonal patterns, with December, February, and October exhibiting greater instability, while the central months of the year showed lower dispersion. The structural change in the market from 2021 onwards was attributed to a combination of factors, including extreme weather events (frosts and droughts), post-pandemic logistical disruptions, exchange rate fluctuations, and expectations related to climate change. The results highlight a scenario of increased risk for producers and agents in the coffee chain, reinforcing the need for risk management tools and public policies focused on climate adaptation and sector resilience. It is concluded, therefore, that the arabica coffee market has undergone a structural rupture, marked by the transition from a stable scenario to a volatile environment, which demands adaptive strategies and greater governance to ensure the long-term sustainability of the production chain. DOI: https://doi.org/10.56238/edimpacto2025.090-086